Perhitungan Harga Pokok Produksi dengan Metode Harga Pokok Pesanan (Job Order Costing) pada Hana Digital Printing Malang - WIDYA, TRI RAHAYU (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The calculation of the cost of production is very important for companies to determine the selling price of a product and assist management in calculating the company's financial statements. The calculation of the cost of production will make it easier to control the company's production costs precisely and quickly so that the company's selling price and profit and loss can be predicted as expected. This study aims to find out whether the implementation of the cost of production using the Job Order Costing method by Dhana Digital Printing Malang has been implemented properly. This study uses a descriptive qualitative method with a case study approach (Case Study) which aims to determine the application of the calculation of the cost of production of agenda books and calendar production at Dhana Digital Printing Malang. Data collection was carried out through observation, interviews and documentation on the object of the full costing and variable costing calculation methods. From the results of the study indicate that the company applies the Job order costing method based on orders. The classification of costs is in accordance with the existing theory, but in calculating overhead costs, the company does not include depreciation costs for machinery and equipment depreciation costs in the calculation of Factory Overhead Costs. For this reason, Dhana Digital Printing can make corrections to the job order costing method by identifying and calculating raw material costs, direct labor costs and factory overhead costs so that the predetermined selling prices can be accurate and increase.